The Painted Ceiling in the Church of St Mary, Grandtully - Graham, Angus (Proceedings of the Society of Antiquaries of Scotland, 1943)
The seventeenth-century ceiling is now threatened by damage from the weather and has prompted a full description. The scheme of the decoration is built upon one large central panel and twenty-eight smaller ones of different sizes and shapes. The panels are set on highly ornate cartouches and are connected with one another by parti-coloured bands; some' contain heraldic achievements, monograms, etc., four depict the Evangelists, and the remainder are devoted to what seem to be biblical subjects, with texts in their margins.